The Roman Catholic Monastic Orders in Eastern Galicia in the Early 20th Century - Zhernokleyev, Oleg (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
This study involves the analysis of the overall quantitative, structural and sociodemographic characteristics of the Roman Catholic monastic Orders in Eastern Galicia as a part of the Galician Crown land of Austria-Hungary in the early 20th century. In the second half of the 19th century, the Roman Catholic monastic communities renewed their activity after a period of decline in the epoch of Enlightenment. The analysis indicates two features that characterize the contemporary Galician monastic Orders – a significant predominance of female members and active social work among the population of the region. Quantitatively, the Roman Catholic monastic structures considerably exceeded those of the Greek Catholic Church